Antibacterial Activity of Extract Ethanol Bidara Leaves (Ziziphus spina-Christi L) on Enteropathogenic coli - Sri Mulyani1 , Merryana Adriani 2, Bambang Wirjatmadi2 (Institute of Medico-legal Publications Pvt Ltd, 2021)
Prokaryotic bacteria are microorganisms can beneficial as normal flora, but also can have health due todisease pathogens and is for the host. The purpose of this study is to find compounds in extract ethanolbidara leaves those compounds and activities against bacteria Enteropathogenic coli. This study shows theflavonoid compounds and tannin in extract ethanol bidara leaves (Ziziphus spina-Christi L) to minimuminhibitory zone at concentrations 50% and minimum bactericidal at concentrations 75%. The higherconcentration extract ethanol Bidara leaves the larger the drag zone produced. The research is experimentalstudy looking the extract ethanol antibacterial activity Bidara leaves with the methods in vitro test diffusion.This study found a chemical compound which is found in extract ethanol Bidara leaves (Ziziphus spinaChristi L) is flavonoid and tannin have antibacterial activity106 CFU/ml against bacteria Enteropathogeniccoli to minimum inhibitory zone at concentrations 50% and minimum bactericidal at concentrations 75%.